Chapter Angiola D'Orso ante lo cómico calderoniano: Amore, honore e potere - Leonetti, Francesca (Studi e saggi, 2020)
This contribution aims to offer a study of the Italian adaptation of the Calderonian comedy Amor honor y poder by Angiola D'Orsi, in which the mechanisms that have allowed the recreation of the semantics of comedy, complex and strongly rooted in the stereotyped formulas of every literary tradition, are highlighted. Art comedian, dramatist, translator and highly experienced actor-manager (capocomico), Angiola D'Orsi shows her ability to acclimate the Spanish opera to the new context of reception, through an operation of mediation and interpretation of the two ideological and dramatic systems. Through the comparative analysis of the figures carrying comedy, characterized by linguistic and character stereotypes, we examine the ways in which their dramatic and cultural redefinition is carried out, closely linked to Italian theatrical practice and in accordance with the traditional mask of Zanni.